ANALISIS KEPUASAN MASYARAKAT TERHADAP PELAYANAN PUBLIK DI BADAN PELAYANAN PERIZINAN TERPADU DAN PENANAMAN MODAL (BP2TPM) KOTA BANJARMASIN - umar makawi; abdul haliq (UPT Publikasi Dan Pengelolaan Jurnal Universitas Islam Kalimantan MAB Banjarmasin, 2018)
The purpose of this study was to determine the level of community satisfaction with the public services provided by the Integrated Licensing Public Service Agency and Investment (BP2TPM) of Banjarmasin City, besides that it was also intended to find out the differences in community characteristics, such as age and level of education with satisfaction with service public. This study uses a quantitative approach, with a sample of 60 people, while the data analysis uses Chi Square Goodness Of Fit and Chi Square Test Of Independence. The results showed that the bureaucracy services provided by BP2TPM, most respondents 30% argued that they were quite satisfied with the licensing services provided by the agency. In addition there are significant differences between gender and community satisfaction, other results show there is no difference between age and community satisfaction, this means that the performance of the service units at BP2TPM does not discriminate or differ in providing services to the community in terms of age level. As well as there is no difference between the level of education and community satisfaction, this means that the service at BP2TPM does not discriminate in providing services to the community.